Inclusão, exclusão e cidadania como desafio para a política em regiões de modernidade periférica - MATHIS, Armin (2012)
Social exclusion is more and more emphasized in the political discourse in Brazil. Political action, in this field, is strongly aimed at creating legitimacy for the social system itself. Within this process of legitimacy creation, the political system claims more responsibility for itself, despite its failure in achieving an effective implementation. This fact is observed through the comparison between a semantic amplification of the concept of citizenship and the empiric reality of human rights violations in the State of Pará, mainly focusing on the actions towards citizenship and impaired people. The governmental intervention, however, has not been able to halt the multiple exclusion process that resulted from the `blind' action of functional systems in modern society.